2021
DOI: 10.1002/lary.29876
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Tonsillectomy Ibuprofen: Is There a Dose‐Dependent Bleeding Risk?

Abstract: Objectives/Hypothesis Post‐tonsillectomy hemorrhage (PTH) is a potentially life‐threatening complication. A recent meta‐analysis suggests that ibuprofen may increase the risk of PTH. The aims of this study were to 1) re‐evaluate the effect of ibuprofen on PTH given additional recent evidence and 2) to evaluate a potential dose effect of ibuprofen. Study Design Meta‐analysis and meta‐regression; single‐institution retrospective review. Methods We conducted a systematic review of the literature and a meta‐analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Ibuprofen is widely used as a first choice NSAID ( 65 ). There is no evidence that NSAIDs increase the risk of postoperative bleeding ( 66 , 67 ). The value of intravenous dexamethasone in the postoperative phase is controversial and it is not frequently used ( 68 , 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ibuprofen is widely used as a first choice NSAID ( 65 ). There is no evidence that NSAIDs increase the risk of postoperative bleeding ( 66 , 67 ). The value of intravenous dexamethasone in the postoperative phase is controversial and it is not frequently used ( 68 , 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is because celecoxib, a selective COX-2 inhibitor, does not affect platelet aggregation and is hence a safe medication with a low risk of side effects when used to treat pain following otolaryngologic procedures. Moreover, a 2022 meta-analysis by Losorelli et al 32 investigated ibuprofen for posttonsillectomy haemorrhage and found no significantly increased risk of haemorrhage with ibuprofen. Krishna et al 33 in their meta-analysis reported no increased risk of bleeding for nonaspirin NSAIDs as well.…”
Section: Discussionmentioning
confidence: 99%
“…ENT surgery, with specific reference to tonsillectomy, was left out from this indication, due to the risk of Post-Tonsillectomy Hemorrhage (PTH) which is a potentially life-threatening complication. Nonetheless, a recent systematic review of the literature and a meta-analysis reported that when ibuprofen is prescribed at the low or high range of commonly used clinical dosages no statistically significant increased risk of PTH [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Board speculate that the low dose of ibuprofen contained in the combination could result in a safer drug profile that could warrant the use in ENT surgeries. On the other hand, further studies are needed to determine if there is a clinically relevant dose-dependent difference in PTH with ibuprofen [ 15 ].…”
Section: Discussionmentioning
confidence: 99%